Peran Strategis Selat Malaka dalam Jaringan Perdagangan Global - Adha Dwi Azzahra Hidayat; Zahra Ainun Nisa; Erni Mulyanie (Indonesian Journal of Social Sciences and Humanities, 2026)
The Strait of Malacca is one of the most strategic maritime routes in the world and plays a crucial role in the global trade network. Geographically, it connects the Indian Ocean and the South China Sea, linking major economic regions such as East Asia, the Middle East, and Europe. This study aims to analyze its strategic role in global trade, particularly in energy distribution and its economic implications for Southeast Asian coastal countries. This research employs a literature review method using secondary data from journals, books, and official reports. The results indicate that the Strait of Malacca serves as a primary route for international shipping, facilitating the transport of crude oil, liquefied natural gas, and manufactured goods. This activity significantly contributes to the economic growth of Indonesia, Malaysia, and Singapore, especially in port and logistics sectors. However, high traffic volume also poses security and navigation risks, requiring strong regional cooperation and effective maritime governance.